Tea polyphenols protect mice from acute ethanol-Induced liver injury by modulating the gut microbiota and short-chain fatty acids. (December 2021) - Sun, Yue; Kang, Kai; Li, Yi-Ling; Sang, Li-Xuan; Chang, Bing
Graphical abstract: Highlights: Effect of tea polyphenols (TPs) protected against acute alcoholic liver injury were tested. TPs remarkably influenced gut microbiota composition and abundance. TPs significantly increased the amounts of Porphyromonadaceae and Coriobacteriaceae at the family level. TPs elevated the abundance of propionic acid, butyric acid and valeric acid in ethanol gavaged mice. The strong correlation between gut microbiota abundance and short-chain fatty acids levels were observed. Abstract: Tea polyphenols (TPs), naturally present in green tea, have a number of health benefits, such as alleviating hepatic injury. Acute alcoholic liver injury was induced in C57BL/6 male mice by 40% ethanol gavage, and the mice were treated with distilled water or TPs in drinking water (4 g/L, 0.4%) for 8 weeks. The results demonstrated that TPs intake alleviated acute alcoholic liver injury and modulated the gut microbiota composition and abundance. TPs supplementation elevated the abundance of propionic acid, butyric acid and valeric acid in ethanol-gavaged mice. Enterorhabdus, Parvibacter, Desulfovibrio, Saccharibacteria_genera_incertae_sedis, Barnesiella, Eubacterium, and Clostridium XVIII showed positive correlations with short-chain fatty acids (SCFAs). Our study confirmed that TPs can alleviate acute alcoholic liver injury by altering the composition of the gut microbiota and SCFAs.